UHPLC-Q-Orbitrap-MS-Based Metabolomics Reveals Chemical Variations of Two Types of Rhizomes of Polygonatum sibiricum - Gelian Luo; Junhan Lin; Weiqing Cheng; Zhibin Liu; Tingting Yu; Bin Yang (Molecules, 2022)
The rhizomes of Polygonatum sibiricum are commonly consumed as food and also used as medicine. However, the metabolic profile of P. sibiricum has not been fully revealed yet. Recently, we developed a novel evergreen species of P. sibiricum. The objectives of this study were to compare the metabolic profiles of two types of P. sibiricum, i.e., the newly developed evergreen type (Gtype) and a wide-type (Wtype), by using UHPLC-Q-Orbitrap-MS-based untargeted metabolomics approach. A total of 263 and 258 compounds in the positive and negative modes of the mass spectra were tentatively identified. Distinctively different metabolomic profiles of these two types of P. sibiricum were also revealed by principal component analysis (PCA) and principal coordinates analysis (PCoA). Furthermore, by using partial least squares discriminant analysis (PLS-DA) modeling, it was found that, as compared with Wtype, Gtype samples had significantly higher content of oxyberberine, proliferin, alpinetin, and grandisin. On the other hand, 15 compounds, including herniarin, kaempferol 7-neohesperidoside, benzyl beta-primeveroside, vanillic acid, biochanin A, neoschaftoside, benzyl gentiobioside, cornuside, hydroxytyrosol-glucuronide, apigenin-pentosyl-glucoside, obacunone, 13-alpha-(21)-epoxyeurycomanone, vulgarin, digitonin, and 3-formylindole, were discovered to have higher abundance in Wtype samples. These distinguishing metabolites suggest the different beneficial health potentials and flavor attributes of the two types of P. sibiricum rhizomes.